The Effect of Weight Loss in Obese Patients with Chronic Stable Plaque-Type Psoriasis - Wanjarus Roongpisuthipong; Marinya Pongpudpunth; Chulaporn Roongpisuthipong; Natta Rajatanavin (Hindawi Limited, 2013)
Background. Chronic plaque psoriasis is frequently associated with obesity. The effect of a low-calorie diet on psoriasis has not been investigated. Objective. The objective was to investigate whether moderate weight loss increases the therapeutic response to topical treatment in obese patients with chronic stable plaque-type psoriasis. Material and Method. A 24-week clinical trial was conducted in 10 patients. The efficacy of a low-calorie diet with topical treatment was compared with baseline in obese patients with chronic stable plaque-type psoriasis. The primary measure of clinical response was the Psoriasis Area and Severity Index at weeks 12 and 24. Results. At week 12, the mean reduction in body weight was 9.6 percent. There was an improvement from baseline of 50 percent or more in the Psoriasis Area and Severity Index in 50 percent of the patients. The responses as measured by improvements in the Psoriasis Area and Severity Index were paralleled by improvements in global assessments by the physician and the patients and in the Dermatology Life Quality Index. Conclusion. Obese patients with chronic stable plaque-type psoriasis increase their response to a low-calorie diet. Lifestyle modifications, including a low-calorie diet, may supplement the pharmacologic treatment of obese psoriasis patients.